Neutron irradiation of silicon diodes at temperatures of +20°C and -20°C - Anghinolfi, F; Bardos, R; Bates, S; Bonino, R; Clark, A; Claussen, N; Fretwurst, E; Glaser, M; Gorfine, G; Gossling, C; Heijne, E; Jarron, P; et al. (1993)
We report measurements of the behaviour of silicon diodes when exposed to integrated neutron doses of up to 5×1013 neutrons/cm2. The measurements have been made at diode temperatures between room temperature and -20°C. From measurements of the diode leakage current and depletion voltage, and consequent evaluations of the effective impurity concentration, the temperature dependence of these quantities is discussed in terms of the annealing behaviour of the diodes. Comments are made on the suitability of silicon as a detector medium for particle physics experiments at future accelerators.